The Influence of Brand Publications on Perceived Creativity, Positive Emotions, and Affective Commitment toward Interaction Intention on Instagram: Evidence from Students at a Private University in Indonesia - Dinda Mahmudah Rahmayanti (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
This study examines the influence of brand publications on perceived creativity and positive emotions through Instagram, and how these factors drive followers’ affective commitment and interaction intentions. A non-probability purposive sampling technique was employed, targeting active students at a private university in Yogyakarta who follow Uniqlo Indonesia’s official Instagram account. Data were collected through an online questionnaire, yielding 229 valid responses and 42 pre-test responses. Structural Equation Modeling (SEM) with AMOS was used for data analysis. The results indicate that perceived creativity positively and significantly influences positive emotions and affective commitment. Furthermore, positive emotions significantly affect affective commitment and interaction intention, while affective commitment also demonstrates a significant positive effect on interaction intention.